A Guideline of to Reduce Transportation Cost: A Case study of A Transport Co., Ltd. - Taengphukieo, Ratchada; Issarapong, Nutthanan; Khamla, Pornsiri; To-on, Piyanat (Frontiers in Engineering Innovation Research, 2020)
This research was a guideline to reduce transportation cost. The cost of fuel becomes a main and highest cost for delivering goods. Therefore many enterprises try to find a strategy to reduce a fuel cost as much as possible, for example, using gas instead of diesel fuel or controlling a driver to drive in a specified route etc. The research methodology began with collecting data and comparing fuel expenditure of A Transportation Co., Ltd. as a case company. From the study, it found that there were 2 types of payment used to manage the transportation operation; (1) actual payment and (2) pay per trip. According to one-month data collecting, the total cost of type (2), pay per trip spent lower that the total cost of type (1), actual payment as 21.91 percent.